NANOTECHNOLOGY: A RAY OF HOPE IN MEDICAL FIELD WITH A SPECIFIC FOCUS IN CANCER - Shruti Sharma (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
The use of nanotechnology is becoming more and more prevalent in medicine as well as in our daily lives. Till date, nanoparticles are the most promising method for delivering large amounts of drugs precisely and directly to cancer cells; as a result, several of these nanomaterials have been developed. These range from basic nanoagents to complex smart devices used for imaging or medication administration. Due to their vast surface area, nanomaterials often allow for the incorporation of many moieties on the surface for either additional functions or targeting. In addition to only utilizing particles for imaging, they can also carry a therapeutic drug as a payload. A theranostic agent is produced and both are combined inside the same particle. The sophistication of highly developed nanotechnology targeting techniques offers a potential avenue for clinical applications in cancer and may enhance the utility of otherwise sub-optimal formulations. This review will cover nanotechnology in both imaging and treatment, offering a broad picture of the subject and its effects on cancer imaging and treatment.